2018
DOI: 10.1556/018.69.2018.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the responses to NaCl stress of three tomato introgression lines

Abstract: We aimed to examine the response of three tomato introgression lines (IL925.3, IL925.5 and IL925.6) to NaCl stress. These lines originated from a cross between M82 (Solanum lycopersicum) and the wild salttolerant tomato Solanum pennellii, each line containing a different fragment of the S.pennellii genome. Salt-sensitive phenotypes related to plant growth and physiology, and the response of antioxidants, pigments and antioxidant enzymes were measured. In general, salt stress decreased the fresh weight of leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The carotenoid and chlorophyll assay, which was conducted in this experimental study, showed a saltrelated decrease in carotenoids, chlorophyll a and total chlorophylls. Ozturk et al [47] showed that salt also significantly decreases chlorophyll a, total chlorophyll a and β-carotene content in pea, which is the same in tomato [48]. At the same time, addition of GA3 to culture medium with NaCl did not improve chlorophyll status of leaves, but decreased it further compared to that of leaves treated with salt.…”
Section: Discussionmentioning
confidence: 98%
“…The carotenoid and chlorophyll assay, which was conducted in this experimental study, showed a saltrelated decrease in carotenoids, chlorophyll a and total chlorophylls. Ozturk et al [47] showed that salt also significantly decreases chlorophyll a, total chlorophyll a and β-carotene content in pea, which is the same in tomato [48]. At the same time, addition of GA3 to culture medium with NaCl did not improve chlorophyll status of leaves, but decreased it further compared to that of leaves treated with salt.…”
Section: Discussionmentioning
confidence: 98%
“…The intensification of various abiotic stresses has been changed into a major threat to the sustainable production of agricultural crops [ 4 6 ]. Plants show physiological, biochemical, and genetic responses to salinity stress [ 7 , 8 ]. Because of its ability to compete with essential materials, NaCl is one of the most vital factors of soil salinity, which leads to a lack of several nutrients in the plants, and causes toxicity of plants [ 9 ].…”
Section: Introductionmentioning
confidence: 99%